Análise da composição e da distribuição geográfica da avifauna das restingas do Estado do Rio de Janeiro - Reis, Henrique Bastos Rajão (1998)
Three patterns of distribution were recognized: wide south-American distribution (85,31 %), Atlantic Forest endemics (14%) and study area endemics (0,69%). The dominance of widely distributed elements, those found at more than two morphoclimatic domains, shows that the studied avifauna is composed by generalists species, which use a great variety of ambients. However, rather than being an avifauna originated from many biomes, the avifauna of the study area seems to be an Atlantic Forest avifauna. The strong influence of the Atlantic Forest avifaunal elements is confirmed by the presence of the endemics and by the comparison with some disturbed lowland Atlantic Forest areas, in Rio de Janeiro state. The community composition is distinguished by the dominance of the suborder Oscines and superfamily Tyrannoidea, defining an open areas avifauna. However, the similarity with lowland forests in Rio de Janeiro state shows that the Restinga avifauna is typicaly a forest edge one. The low specificity may be explained by the history of successive Restinga drowning during the Holocene and by the lack of geographical barriers with other Tropical Atlantic Domain formations.